Edge-Site Selective Decoration of Silver Nanoparticles on tio2 Nanosheets for the Rapid Catalytic Reduction of Nitroarenes - Singh, D (Elsevier Ltd, 2024)
In this study, we aim to construct an edge-site selective deposition of silver nanoparticles on TiO2 nanosheets (Ag-TiO2NSs) for the catalytic reduction of toxic nitroarenes (NAs) using NaBH4 medium. The as-prepared Ag-TiO2NSs were characterized by various analytical techniques such as XRD, HR-TEM, SEM-EDAX, elemental mapping and XPS analyses. The HR-TEM images confirmed that the Ag nanoparticles (AgNPs) size of around 3.05 ± 0.5 nm in diameter exhibited the selective growth specifically on the edges of the TiO2NSs. Additionally, it was observed that the TiO2NSs exhibited a high exposure of (101) facets. The prepared Ag-TiO2NSs catalyst exhibited remarkably high catalytic activity in the reduction of 4-nitrophenol (4-NP) (∼6 min, Kapp: 9.2 × 10−3 s−1 and TOF: 1.13 × 10−6 mol mg−1 min−1), which was comparable to or surpassing the catalytic performance of most of the previously reported Ag-based catalysts. Moreover, the catalyst showed an excellent catalytic reduction ability of other NAs such as 4-nitroaniline (4-NA) (∼10 min, 2.8 × 10−3 s−1), 4-(4-nitrophenyl)morpholine (4-NM) (∼8 min, 6.0 × 10−3 s−1), and 4-(2-fluoro-4-nitrophenyl)morpholine (4-FNM) (∼11 min, 4.2 × 10−3 s−1). In addition, the Ag-TiO2NSs exhibited commendable recyclability, with a minimal decrease in the activity over four consecutive recycling operations. The exceptional catalytic performance could be attributed to the smaller size of the AgNPs along with the synergistic effect between AgNPs and their interfacial contact with the (101) facet exposure of TiO2NSs. The Ag-TiO2NSs catalyst demonstrated the potential application for the catalytic reduction of 4-NP in a fixed bed reactor, operating under mild reaction conditions. © 2024 Elsevier Ltd